Towards the innate immunity phenotype of newly emerging viruses - Felgenhauer, Ulrike Elke; Justus Liebig University Giessen (My University, 2021)
The innate immune system, orchestrated by interferons (IFNs), is the host’s first line of defence against intruding viruses. Therefore, pathogenic viruses have evolved a wide variety of IFN-antagonistic strategies. The sensitivity of viruses to IFNs as well as the quality and strength of IFN evasion can be an important determinant of virulence. This work aims to characterize this so-called innate immunity phenotype of newly emerging viruses with zoonotic potential. For this, the novel phlebovirus Ntepes virus (NTPV) of unknown implications for human health was analyzed, as well as the causative agent of the current COVID-19 pandemic, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). NTPV is a novel phlebovirus of unknown pathogenicity that was recently found to infect humans. This work provides the first comprehensive characterization of its innate immunity profile in human cells, compared to the related Rift Valley fever virus (RVFV) and an attenuated RVFV (clone 13), which lacks a functional virulence factor NSs. Thereby, transcriptional IFN and IFN-stimulated gene (ISG) induction upon NTPV infection and its sensitivity to exogenously added type I and type III IFNs were comparable to responses to the avirulent clone 13. Nonetheless, NTPV encoded an NSs which counteracted the promoter transactivation of several innate immune genes, as did three out of four other novel phleboviruses. However, each of the tested NSs proteins exhibited a distinct antagonistic profile, suggesting virus-specific pathways of IFN antagonism. Further, mass spectrometry analyses identifying host cell interaction partners of NSs proteins revealed a considerable overlap of interactors between viruses. Still, distinct host binding partners were identified for each NSs, again implying different ways to manipulate the host cell environment. In summary, NTPV exhibited a lower capability for IFN evasion than the pathogenic RVFV. However, the general ability of NTPV NSs to counteract IFN induction and signalling and its ability to infect humans emphasize the zoonotic potential of NTPV. The recently emerged SARS-CoV-2 is the causative agent of the devastating COVID-19 lung disease pandemic. Here, its innate immunity phenotype was evaluated in comparison to the 2003-emerged SARS-CoV-1. Thereby, SARS-CoV-2 was inhibited by both IFNs of type I and type III in a dose-dependent manner, and generally exhibited a greater IFN sensitivity than SARS-CoV-1. Moreover, SARS-CoV-2 replication was boosted by proposed drug candidate Ruxolitinib, an inhibitor of IFN signalling. Further, only SARS-CoV-2 robustly induced an early antiviral response characterized by the transcriptional upregulation of IFNs, cytokines, and ISGs, which also translates to the protein level. However, this potent antiviral response was limited to the human lung cell line Calu-3, as it was absent or severely diminished in human lung cell lines H1299 and A549-ACE2, respectively. Comparison of the transcriptomic profiles of the three cell lines suggests that Calu-3 cells exhibit a “pre-stimulated” state which could account for the observed imperfect inhibition of innate immune induction in these cells. To conclude, this work showed that SARS-CoV-2 is sensitive to type I and III IFNs and unable to counteract IFN induction in all settings, differentiating it from the highly pathogenic SARS-CoV-1.
Keywords: ddc:570